SUSTAINABLE TOURISM: WHY DO GOVERNMENT NEED COLLABORATIVE GOVERNANCE? - Duadji N.; Tresiana N. (Russian Journal of Agricultural and Socio-Economic Sciences, 2020)
The research aims to elaborate strategic dimensions in collaborative planning as the carrying capacity of government action in the success of sustainable tourism development policies. The criticism of the government's dominance in the tourism sector has marginalized the community and gave rise to psudo democracy. The research method uses descriptive qualitative, located in Pekon Wisata Teluk Kiluan, Tanggamus Regency. Indonesia. Data collection by interview, observation, and documentation study. The analysis uses a collaborative governance model. The results of the study elaborate on the strategic dimensions of collaborative governance in the form of participation, equality and community competence that require policy correction and a strategic part in tourism sustainability. Several supporting factors such as local culture, community education level, government dynamics in responding to change, deliberations for planning and regional development are useful in improving decision making in public policy.